The Relationship Between Negative Life Events and Internet Addiction Disorder Among Adolescents and College Students in China: A Systematic Review and Meta-Analysis - Wang, Jun; Hao, Qing-hong; Tu, Yang; Wang, Yang; Peng, Wei; Li, Hui; Zhu, Tian-min (Frontiers in Psychiatry, 2022)
Objective: Internet Addition Disorder (IAD) has become a social problem. Literature suggests that negative life events can cause numerous problematic behaviors and part of them will result in IAD. However, there is a lack of evidence elucidate the association between negative life events and IAD. Thereby, we performed a comprehensive analysis to further document the relationship between negative life events and IAD among adolescents and college students in China. Methods: We searched ten electronic databases for relevant articles. We extracted correlation coefficient (r) values from each study and calculated 95% confidence interval (95% CI) after applying Fisher’s z. A random-effect or fixed-effect model was applied to analyze the data. Heterogeneity was examined using I2 statistics and the Cochran’s Q statistics. Results: A total of 31 studies were involved in this meta-analysis. Positive correlation was observed between negative life events and IAD. The subtype interpersonal relationship of negative life events was closely associationed with IAD. Conclusion: There were significant positive association between negative life events and IAD.The findings can be used to guide IAD interventions.